Hubungan antara kadar lipoprotein dengan kejadian stroke dan tumor otak - Cut Diana Maya Theresa; Yuneldi Anwar; Alfansuri Kadri (Fakultas Kedokteran USU, 2014)
Background : Recent evidences showed correlation main class of lipoprotein with stroke and brain tumor. Stroke and brain tumor can caused by multifactor, and nutrition is one of their etiology.Objectives : This study aimed to investigate correlation between lipoprotein with stroke and brain tumor.Methods : This was a cross-sectional study, subjects with stroke (26 persons) and brain tumor (26 persons). All patients underwent physical and neurological examinations, neuroimaging and lipoprotein serum examinations. Results : Stroke subjects consisted of 17 (65.4%) women and 9 (34.6%) men, with mean age ±54.38 years. Mean HDL level was 38.96±15.66 mg/dL, mean LDL level was 131.69±32.37 mg/dL, mean VLDL level was 22.42±6.64 mg/dL. The LDL level were significantly correlated with stroke and had a moderate correlation (r=0.426, p=0.030). The HDL level were not significantly correlated with stroke and had a very weak correlation (r=-0.010, p=0.960). VLDL level were not significantly correlated with stroke and had a very weak correlation (r=-0.087, p=0.672). Brain tumor subjects consisted of 16 (61.5%) men and 10 (38.5%) women, with mean age ±46.46 years. Mean HDL level was 38.58±12.73 mg/dL, mean LDL level was 131.42±43.67 mg/dL, mean HDL level was 26.70±10.75 mg/dL. The LDL level were not significantly correlated with brain tumor and had a very weak correlation (r=-0.103, p=0.618). HDL level were not significantly correlated with brain tumor and had a very weak correlation (r=0.087, p=0.672). VLDL level were not significantly correlated with brain tumor and had a very weak correlation (r=0.031, p=0.881).Conclusion : There was a significant correlation between LDL level and stroke, but no significant corelation between HDL levels with stroke and VLDL levels with stroke . The HDL, LDL and VLDL levels were not significant corelation with brain tumor. Keywords : lipoprotein, HDL, LDL, VLDL, stroke,brain tumor